Pengaruh Model Literasi Program 6M Terhadap Hasil Pembelajaran Menulis Cerpen pada Siswa Kelas 4 SDN 235 Palembang - Korima, Anisa; Junaidi, Ilham Arvan; Ayu, Imelda Ratih (Institut Teknologi Pendidikan Indonesia, 2022)
The purpose of this study was to find out how the results of learning to write short stories using the 6M literacy model program for 4th-grade students at SDN 235 Palembang. This type of research is quantitative using a pre-experimental form (onegroup pretest-posttest design). Learning outcomes obtained after the treatment(posttest value) an average of 82.88 at the end of the analysis using the t-test obtained if α = 0.05 and DB = N-1 = 25-1 = 24 obtained = 1, 71088 and = 9,449. If, then H0 is rejected and Ha is accepted so that the average posttest learning outcomes are greater than the pretest. Thus, it can be said that there is an effect of learning outcomes using the 6M Program literacy model on writing books for 4thgrade students of SDN 235 Palembang.